THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE LOYALTY AT PT CATUR SENTRA DUTA (CSD) CONSORTIUM DURI BRANCH - Amanda; Edi Haryono (Journal of Islamic Banking, Economics and Finance, 2025)
This study aims to determine the effect of the work environment on employee loyalty at PT Catur Sentra Duta (CSD) Consortium, Duri Branch. A conducive work environment is believed to play an important role in increasing employee loyalty to the company. The research method used is quantitative with a descriptive correlational approach. The population in this study were all employees of PT CSD Consortium, Duri Branch, with purposive sampling. Data collection was carried out through questionnaires and analyzed using a simple linear regression test. The results of the study indicate that the work environment has a positive and significant effect on employee loyalty. The better the work environment perceived by employees, both in terms of physical conditions, relationships between colleagues, and support from superiors, the higher the level of loyalty shown by employees to the company. Therefore, company management needs to pay attention to creating a comfortable, safe, and supportive work environment so that employee loyalty can be maintained and improved.